Effects of online tDCS and hf-tRNS on reading performance in children and adolescents with developmental dyslexia: a study protocol for a cross sectional, within-subject, randomized, double-blind, and sham-controlled trial - Battisti, Andrea; Lazzaro, Giulia; Varuzza, Cristiana; Vicari, Stefano; Menghini, Deny (Frontiers in Neurology, 2024)
Background: Developmental Dyslexia (DD) is a brain-based developmental disorder causing severe reading difficulties. The extensive data on the neurobiology of DD have increased interest in braindirected approaches, such as transcranial direct current stimulation (tDCS), which have been proposed for DD. While positive outcomes have been observed, results remain heterogeneous. Various methodological approaches have been employed to address this issue. However, no studies have compared the effects of different transcranial electrical stimulation techniques (tDCS and transcranial random noise stimulation, tRNS), on reading in children and adolescents with DD. Methods: The present within-subject, double-blind, and sham-controlled trial aims to investigate the effects of tDCS and hf-tRNS on reading in children and adolescents with DD. Participants will undergo three conditions with a one-week interval session: (A) single active tDCS session; (B) single active hf-tRNS session; and (C) single sham session (tDCS/hf-tRNS). Left anodal/right cathodal tDCS and bilateral tRNS will be applied over the temporo-parietal regions for 20 minutes each. Reading measures will be collected before and during each session. Safety and blinding parameters will be recordered. Discussion: We hypothesize that tRNS will demonstrate comparable effectiveness to tDCS in improving reading compared to sham conditions. Additionally, we anticipate that hf-tRNS will exhibit a similar safety profile to tDCS. This study will contribute novel insights into the effectiveness of hf-tRNS, expediting the validation of brain-based treatments for DD.